2019
DOI: 10.1108/ijis-03-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Research on the influencing factors of entrepreneurial intentions based on mediating effect of self-actualization

Abstract: Purpose Using statistical analysis, this paper aims to understand and investigate the factors for starting a new company successfully. Indicators from the literature and the data analysis prove that entrepreneurial environment, ability, intentions and self-actualization affect the success rate of entrepreneurship. Design/methodology/approach To analyze the success factors for entrepreneurship, the authors take entrepreneurial environment and entrepreneurial ability as the independent variables, self-actualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Competencies related to entrepreneurship include business competencies, conceptual competencies, and attitudes competencies. This finding supports Dong et al (2018) and Daliman et al (2019) that entrepreneurial competency is able to create entrepreneurial intention.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Competencies related to entrepreneurship include business competencies, conceptual competencies, and attitudes competencies. This finding supports Dong et al (2018) and Daliman et al (2019) that entrepreneurial competency is able to create entrepreneurial intention.…”
Section: Discussionsupporting
confidence: 89%
“…quality of knowledge, skills, and attitudes leads these individuals to start businesses (Botha et al, 2019). The involvement of competency in entrepreneurial ability becomes the capital for individuals to realize entrepreneurial intention (Dong et al, 2018) This study examines the effect of personality traits on entrepreneurial competency, personality traits on entrepreneurial intention, entrepreneurial competency on entrepreneurial intention, analyzes the mediating role of entrepreneurial competency on the influence of personality traits on entrepreneurial intention in medium-sized business managers in Bali.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dong et al believed that college students' EA elements include professional skills, market control, business management, and some comprehensive abilities [9]. Lucas and others thought that the element system of EA is mainly composed of four levels: consciousness, knowledge and skills, organization and management, and opportunity discrimination and insight [10].…”
Section: Related Workmentioning
confidence: 99%
“…The study discovered that college graduates' entrepreneurial aim can be highly influenced by their gender, family business position, social practices, and entrepreneurial model, etc., but their place of origin and level of adventure had no discernible influence. The empirical study by Dong et al (2018) demonstrated that the stronger the entrepreneurial culture is, the greater the entrepreneurial intentions of college students are; the greater the entrepreneurial ability is, the greater the entrepreneurial intentions are; and under the mediator variable impact of self-actualization, the greater the business ecosystem is, the greater the entrepreneurial intentions are.…”
Section: Dominant Factors Of Entrepreneurial Intentionmentioning
confidence: 99%